2002
DOI: 10.1046/j.1365-2265.2002.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the PRKAR1A gene in sporadic somatotroph and other pituitary tumours

Abstract: No mutations were found in any of the exons sequenced. Relative mRNA expression was not decreased in any of the sporadic pituitary tumour samples. The present data thus do not suggest a major role for the PRKAR1A tumour suppressor gene in sporadic GH-secreting or other pituitary tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Subsequently, the same genetic defects have been detected in some sporadic endocrine tumors, such as adrenal and thyroid adenomas and carcinomas (16 -18). Conversely, a role of PKA R1A in the pathogenesis of pituitary tumors has been ruled out based on the absence of both gene mutations and loss of heterozygosity reported by previous studies and confirmed in the present series (15,19,20).…”
Section: Discussionsupporting
confidence: 62%
“…Subsequently, the same genetic defects have been detected in some sporadic endocrine tumors, such as adrenal and thyroid adenomas and carcinomas (16 -18). Conversely, a role of PKA R1A in the pathogenesis of pituitary tumors has been ruled out based on the absence of both gene mutations and loss of heterozygosity reported by previous studies and confirmed in the present series (15,19,20).…”
Section: Discussionsupporting
confidence: 62%
“…In each of these cases, the establishment of autonomous hyperproliferative cells may be due to the immortalizing effect of increased PKA signaling, although, as above, there is little impetus toward malignant transformation in the absence of additional mutations. In fact, down-regulation of PRKAR1A has recently been described in sporadic growth hormone-producing adenomas (32), although mutations in PRKAR1A are rarely, if ever, observed in these tumors (33,34).…”
Section: Cancer Researchmentioning
confidence: 99%
“…Although the evidence suggests that this may be the case in CNC, it is not known whether PRKAR1A can cause sporadic pituitary tumors when mutated at the somatic level. Three recent studies [42][43][44] have demonstrated that PRKAR1A is an unlikely molecular etiology of non-familial pituitary tumors, not unlike the case of menin, the MEN 1 gene [45].…”
Section: Is Prkar1a Mutated In Other Pituitary Tumors?mentioning
confidence: 99%